Passive mode-locking in erbium-doped fibre laser based on BN-GO saturable absorber - Ahmad, Harith; Soltani, Soroush; Thambiratnam, Kavintheran; Yasin, Moh; Ismail, Mohammad Faizal; Tiu, Zian Cheak (Taylor & Francis, 2018)
A C-band mode-locked fibre laser incorporating a boron nitride-doped graphene oxide (BN-GO)-based saturable absorber (SA) is proposed and demonstrated. The SA is fabricated by depositing multiple layers of synthesized BN-GO nanoparticles onto the polished surface of a side-polished fibre, which is then inserted into an erbium-doped fibre laser cavity to generate the desired pulsed output. The strong nonlinear optical response and light absorption of the BN-GO nanoparticles induces the generation of a highly stable mode-locked pulse at 1567.32 nm with visible Kelly’s sidebands. The pulses have a measured repetition rate of 13.56 MHz and a pulse width of 1.18 ps at the maximum pump power of 280.5 mW. The pulses have a frequency signal-to-noise ratio of ∼53 dB, indicating a highly stable output. The proposed laser would find significant telecommunications applications, particularly for dense wavelength division multiplexing systems.